Civil Service Management and Administrative Systems in South Asia - Dhakal, Tek Nath.; Jamil, Ishtiaq; Paudel, Narendra Raj. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book examines public administration in South Asia in the context of rapid changes and modernization of administrative traditions, thoughts, and practices. The existing literature has, however, not given adequate attention to these developments, at least in a single volume. The book describes both the shared administrative traditions of Bhutan, Bangladesh, China, India, the Maldives, Nepal, Pakistan, and Sri Lanka, and how far they have adapted their administrative systems to respond to contemporary administrative and governance challenges. The book studies how national civil service reforms have been carried out in each member state of South Asia and how the national civil service acts and different regulations are being implemented, as well as what are the critical factors associated with the implementation of national civil service acts and reform measures in the region. Ishtiaq Jamil is Associate Professor in the Department of Administration and Organization Theory at the University of Bergen, Bergen, Norway. Tek Nath Dhakal is Professor and Head of the Department of Public Administration, Tribhuvan University, Nepal. Narendra Raj Paudel is Lecturer in the Department of Public Administration, Tribhuvan University, Nepal.
Chapter One: Introduction: Understanding Civil Service in South Asia, Ishtiaq Jamil, Tek Nath Dhakal and Narendra Raj Paudel -- Chapter Two: The Civil Service System in Bhutan, Dhurba Rizal -- Chapter Three: The Civil Service System of Bangladesh, Sk.Tawfique M. Haque and M. Mahfuzul Haque -- Chapter Four: Civil Service Management in India, Namrata Singh -- Chapter Five: Civil Service Management in Nepal, Shree Krishna Shrestha and Narendra Raj Paudel -- Chapter Six: The Promise of Representative Bureaucracy and Citizen's Trust in the Civil Service in Nepal, Ishtiaq Jamil -- Chapter Seven: Civil Service Reforms in the Islamic Republic of Pakistan: Progress So Far, Implementation Barriers and Challenges, Imtiaz Badshah and Konstantin Timoshenko -- Chapter Eight: The New Statutory Civil Service in the Maldives: Towards a Decentralized Human Resource Management Model? Mohamed Faizal and Rob Laking -- Chapter Nine: Public Administration in Sri Lanka: An Analysis of Evolution, Trends and Challenges in Personnel Management, Renuka Priyantha, Ranjith Dickwella and Ravindra Gunasekara -- Chapter Ten: The Administrative System in Bangladesh: Reform Initiatives with Failed Outcomes, Pranab Kumar Panday -- Chapter Eleven: Reforms in the Administrative System of Nepal, Bharat Gautam -- Chapter Twelve: The Local Administrative System in India, Jitendra G. Wasnik -- Chapter Thirteen: Public Administration in Sri Lanka: An Inquiry into Structure, Reforms, and Management, K. Liyanage, R. Ramesh and N. Sivakumar -- Chapter Fourteen: The Development of Public Administration in the People's Republic of China: An Analysis of Administrative Reform, S.Baskaran and Mr. M.M. Ihjas.
Keywords: Asia-Politics and government; Legislative bodies; Political communication; Political science; Public policy; Public Policy; Asian Politics; Governance and Government; Legislative and Executive Politics; Political Communication